2017
DOI: 10.1186/s13104-017-2698-2
|View full text |Cite
|
Sign up to set email alerts
|

Early occurrence of childhood dental caries among low literate families

Abstract: ObjectiveThe purpose of this cross-sectional study was to identify the oral health status and influencing factors in preschool children in Tabriz, Iran. A total of 756 children from 20% of the total district preschools were selected using a two-step random sampling procedure. Questionnaires were used to collect demographic and socio-economic data. Oral exams were conducted by a single pediatric dentist to assess the children’s oral health, and to determine the number of decayed, missing, and filled teeth (dmft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Increased age was associated with a higher risk of caries in 19 studies across eight countries [ 20 , 21 , 23 , 26 , 28 , 31 , 33 , 37 , 43 , 45 , 46 , 55 , 57 , 69 , 73 , 77 , 78 , 80 , 82 ]. Nine studies reported a higher risk of dental caries in males [ 18 – 21 , 27 , 35 , 36 , 47 , 85 ], while females were reported to have a higher caries risk in six studies [ 26 , 30 , 31 , 50 , 55 , 65 ]. Weight status was significantly associated with caries in nine studies, of which four studies reported positive associations between high BMI/overweight and caries [ 25 , 30 , 55 , 56 ] and two studies reported an inverse association between BMI and dental caries [ 47 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased age was associated with a higher risk of caries in 19 studies across eight countries [ 20 , 21 , 23 , 26 , 28 , 31 , 33 , 37 , 43 , 45 , 46 , 55 , 57 , 69 , 73 , 77 , 78 , 80 , 82 ]. Nine studies reported a higher risk of dental caries in males [ 18 – 21 , 27 , 35 , 36 , 47 , 85 ], while females were reported to have a higher caries risk in six studies [ 26 , 30 , 31 , 50 , 55 , 65 ]. Weight status was significantly associated with caries in nine studies, of which four studies reported positive associations between high BMI/overweight and caries [ 25 , 30 , 55 , 56 ] and two studies reported an inverse association between BMI and dental caries [ 47 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…Table 3 describes the statistically significant determinants related to family background, such as socioeconomic, sociodemographic, geographical location, school type (private or public), and parents’ education level, as potential risk factors contributing to dental caries. A total of 20 studies found negative associations with maternal education (13 studies) [ 21 , 26 , 29 , 31 , 37 , 52 , 57 , 58 , 60 , 67 , 81 , 83 , 89 ], paternal education (3 studies) [ 24 , 27 , 50 ], or education of both parents combined (4 studies) [ 20 , 38 , 40 , 42 ] (Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…in the study by Fatemeh Khani-Varzegani et l, only 15.2% of preschool children had decay free teeth, that is 17.2% boys and 13.1% girls. The study conducted by lahore et al, showed a 33.3% prevalence of caries in 3 years children, 47.6 and 75% in 4 and 5-year-olds (Khani-Varzegani et al, 2017).…”
Section: Resultsmentioning
confidence: 92%
“…it is considered one of the most prevalent diseases in childhood, affecting 50 to 90% of children globally (Mathew, 2020a). early childhood caries are associated with pain and tooth loss as well as impaired growth, decreased weight and negative effects on speech (Khani-Varzegani et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…25 In Iran, 4-7 year-old school children showed that 84.9% had dental caries. 26 Although there is a wide variation of ECC prevalence across countries, it remains prevalent in most countries worldwide. 13 A study done in Lagos showed a prevalence of 21.2%; however the prevalence of ECC increased with age and for children aged 61-71 months was 35.4%.…”
Section: Prevalence Of Eccmentioning
confidence: 99%